Guatemalan Teenagers’ Hopes and Dreams: A Qualitative Study of Drawings and Characteristics of Future Selves - Ashdown, Brien (2022)
Utilizing adolescents' drawings in order to investigate their perceptions of self has a long history in psychology. The methodological approach is particularly useful in places, such as Guatemala, where the population may have relatively lower levels of literacy and/or less experience engaging with Western-style research surveys. By asking adolescents to draw a picture of themselves and list five characteristics that they hope to have in 15 years, we were able to collect valuable data on issues such as the students' desires for the future and what they see as possible for themselves. Participants (N = 81, Mage = 14.56 years, 49.4% cisgender girls, all from Jocotenango, Guatemala) provided five characteristics that they hoped to have 15 years in the future, and then drew a self-portrait of themselves 15 years in the future. The drawings and characteristics underwent a process of thematic analysis to determine patterns and themes that are prevalent in the data. Common themes that emerged among the characteristics include jobs or specific professions they hope to have, owning a home or property such as a car, and having a family. In the drawings, the common themes are similar: mentioning specific careers, owning a home or property, and having a family. This data can help us determine what type of futures these students hope for in order to ensure that schools and other institutions are providing the tools students will need for those futures.